2013
DOI: 10.1016/j.envsci.2012.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Making sense of policy implementation: The construction and uses of expertise and evidence in managing freshwater environments

Abstract: Publisher's copyright statement: NOTICE: this is the author's version of a work that was accepted for publication in Environmental Science and Policy. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be re ected in this document. Changes may have been made to this work since it was submitted for publication. A de nitive version was subsequently published in Environmental Science and Policy, 30, June 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…process is the assumption that expertise is held in particular individuals or institutions, and that it is value free. However, as social science research has demonstrated, the nature of evidence, ideas, arguments and framing all matter in the way in which expertise is determined and used in the process of environmental governance (Jasanoff 2003;Owens, 2010;Bracken and Oughton, 2013). As such, expertise is not self-evident but rather determined by both 'what' is going to count as relevant knowledge and subsequently 'who' then possesses such knowledge to inform policy debates within the public arena (Gieryn, 1999;Jasanoff, 2003, Eden et al, 2006.…”
Section: Multiple Softwares: Expertise and Community Engagement In Thmentioning
confidence: 99%
“…process is the assumption that expertise is held in particular individuals or institutions, and that it is value free. However, as social science research has demonstrated, the nature of evidence, ideas, arguments and framing all matter in the way in which expertise is determined and used in the process of environmental governance (Jasanoff 2003;Owens, 2010;Bracken and Oughton, 2013). As such, expertise is not self-evident but rather determined by both 'what' is going to count as relevant knowledge and subsequently 'who' then possesses such knowledge to inform policy debates within the public arena (Gieryn, 1999;Jasanoff, 2003, Eden et al, 2006.…”
Section: Multiple Softwares: Expertise and Community Engagement In Thmentioning
confidence: 99%
“…Floods and their management tend to be interpreted in a specific way that is partly dictated by legislation, which is in turn related to a certain jurisdiction, which then informs and influences practice. Individuals and organisations themselves in turn interpret legislation and plans in different ways according to personal and local priorities (Bracken and Oughton 2013). There is a vast literature outlining different approaches to FRM, but also research that questions the prevailing interpretations of what flood management should be, how it should be assessed, and, therefore, how it should be practiced (Werritty 2006;Rouillard et al 2015).…”
Section: The Role Of Borders In Flood Risk Management (Frm)mentioning
confidence: 99%
“…We know that for beneficial outcomes, top-down, technical approaches must be balanced with bottom-up, participatory knowledge (Bracken & Oughton 2013;Cinderby et al 2011), that communication is critical, and that knowledge production and knowledge communication are intertwined (Callon 1999). What presents problems is the application of these ideals in a world where experts and the public are growing more aware of the complexity of the "social-ecological" (e.g.…”
Section: Introductionmentioning
confidence: 99%